Design and improvise of high reach wire cutter - Esam, Asrizam; Kamarudin, Norliyana; Monir, Norazlin; Md Halid, Hidayah; Ab Ghani, Muhamad Amin; Muhd Feisal Ismail, Albert Feisal; Che Hassan, Muhammad Firdhaus (Kalahari Journals, 2022)
High reach wire cutter is an apparatus design using a new mechanical technique of wire cutter without string-pulling or lever mechanism. Galvanized steel wire usually use to bind the advertisement buntings on certain high on street lighting columns in Malaysia side road. Difficulties to dismantle the bunting or leftover rusted wire that need to use a ladder can cause some risk, and it disrupts the scenery of the environment. On the other hand, the old rusted wire is left on the street lighting columns due to the dumping of illegal advertisements in the residential areas. The challenges of ladder perturbation cause the wire is tied at more than 4.0 meters height prompting the workers to snatch the buntings down, leaving the wire fragments on the posts. This study is to design and improvise tools that can reach the higher, speeding the process, low cost, light, adjustable handle and avoided using a ladder to improve safety. The result is successfully developing a high reach wire cutter with a new mechanism with buffer to fill in the gap and column retainer to make it efficiently cut and remove tight wire on the street lighting columns.